2017
DOI: 10.3390/foods6110093
|View full text |Cite
|
Sign up to set email alerts
|

Glycomacropeptide Reduces Intestinal Epithelial Cell Barrier Dysfunction and Adhesion of Entero-Hemorrhagic and Entero-Pathogenic Escherichia coli in Vitro

Abstract: In recent years, the potential of glycosylated food components to positively influence health has received considerable attention. Milk is a rich source of biologically active glycoconjugates which are associated with antimicrobial, immunomodulatory, anti-adhesion, anti-inflammatory and prebiotic properties. Glycomacropeptide (GMP) is the C-terminal portion of kappa-casein that is released from whey during cheese-making by the action of chymosin. Many of the biological properties associated with GMP, such as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…IgG α-(2→6)linked sialylation is associated with decreased inflammation following Fc receptor binding (Marth & Grewal, 2008). Sialic acid on other milk glycoproteins is thought to play important roles in binding E. coli and Salmonella enteritidis (Feeney, Ryan, Kilcoyne, Joshi, & Hickey, 2017;Nakajima et al, 2005), promoting the growth of the bifidobacteria strains such as Bifidobacterium breve, B. bifidum, and B. infantis (Idota, Kawakami, & Nakajima, 1994), preventing Helicobacter pylori colonization (Wang et al, 2007), inhibiting haemagglutination by the influenza virus (Kawasaki et al, 1993), and promoting calcium-binding properties (Jaques, Brown, Barrett, Brey, & Weltner, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…IgG α-(2→6)linked sialylation is associated with decreased inflammation following Fc receptor binding (Marth & Grewal, 2008). Sialic acid on other milk glycoproteins is thought to play important roles in binding E. coli and Salmonella enteritidis (Feeney, Ryan, Kilcoyne, Joshi, & Hickey, 2017;Nakajima et al, 2005), promoting the growth of the bifidobacteria strains such as Bifidobacterium breve, B. bifidum, and B. infantis (Idota, Kawakami, & Nakajima, 1994), preventing Helicobacter pylori colonization (Wang et al, 2007), inhibiting haemagglutination by the influenza virus (Kawasaki et al, 1993), and promoting calcium-binding properties (Jaques, Brown, Barrett, Brey, & Weltner, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…This carbohydrate-containing compound can survive gastric transit without hydrolysis and is absorbed intact into the bloodstream [16,17]. Even if 30 years ago GMP was considered as a source of energy, it now becomes obvious that it has also the potential of modulating various biological processes, including binding of cholera toxin and E. Coli enterotoxins, inhibition of bacterial and viral adhesion, suppression of gastric secretion, and promotion of bifidobacterial growth [18][19][20][21][22]. The anti-inflammatory and immunomodulatory effects of GMP have been reported in rodent models of inflammatory bowel disease [23,24], murine spleen and bone marrow dendritic cells [25,26], as well as in lymphocytes and macrophages [27].…”
mentioning
confidence: 99%
“…Besides, it has been reported that GMP generates dose-dependent inhibition of enterotoxigenic E. coli (ETEC) K88 adhesion to ileal mucosa in vitro [12]. Finally, a recent report showed that GMP also prevents the attachment of several strains of EHEC and EPEC to Caco-2 and HT-29 mammalian cells [13]. In this study, it was demonstrated that GMP, beyond inhibiting bacterial adhesion, is able to maintain the structural integrity of tight junctions on Caco-2 monolayers, thus delaying the paracellular translocations of EPEC.…”
Section: Biological Activities Of Gmpmentioning
confidence: 99%